Expression of histone deacetylase-1 and p300 in aristolochic acid nephropathy models. (27th June 2014) - Tian, Yahui; Yang, Yaohui; Gao, Lei; Zhao, Haijiao; Peng, Xiaolan; Zhang, Zhongwen; Wu, Guojuan
Abstract: Aristolochic acid nephropathy (AAN) is mainly caused by aristolochic acid I (AAI), but the actual mechanism is still uncertain. The current study explored the correlation among the expression of Smad7, p300, histone deacetylase-1 (HDAC1) and the development of AAN using transmission electron microscopy (TEM), RT-PCR, and western blotting in the AAN mouse model and in the AAN cell model. TEM revealed that the renal tubular epithelial cells from the AAI-treated mice presented organelle damages and nuclear deformation. We found that a certain dose of AAI caused renal fibrosis and induced renal tubular epithelial cells to differentiate into myofibroblasts. There was a gradual increase in the expression of HDAC1 mRNA and protein observed using RT-PCR and western blotting in the AAN cell model compared with the control group. Gradual decrease in the expression of Smad7 and p300 mRNA and protein was revealed in the AAN mouse and cell models compared with the control group. These results suggest that AAI dose dependently contributed to the development of AAN, and HDAC1 and p300 participate in the modulation of TGF-β/Smad pathway-mediated renal interstitial fibrosis.